Menggagas Efektivitas Manajemen Khas Indonesia dalam Konteks Globalisasi - - Supardi (Unisia, 2004)
Globalization performs as a new form of imperialism. Every single entities, such as bussiness, military, govenment, and education, are challanged. in order to maintain their effectiveness, they have to be adjusted based on the trend of globalization. in bussinees, as the main topic of this essay, will suffer multiple pressure, first, global market consequences, second, local politics and culture and third, internal condition of enterprises. Therefore, in responding such pressure, "blance solution" is absolutely needed, in magerial skills, this solution is made through creating combination between culktural skill and managerial skill. Here, the discussion on "Indonesian Management Model" is absolutely relevant.